World War II - Williams, Brian, 1943- (DK findout!, 2017)
"Discover World War II facts and hear from people who lived through the war that shaped the modern world, from the cause of the conflict to the most important battles. From the prewar rise of Nazi Germany to the start of the war with the invasion of Poland in 1939 to the end of the war in 1945 and the Nuremburg Trials, all aspects of the deadliest conflict in human history are covered in great detail in DK findout! World War II with content that is accessible and appropriate for children 6-9 years old."-- provided by publisher.